2019
DOI: 10.1159/000505146
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Extracorporeal Therapy Collaborative Device and Timely Support for Endotoxic, Septic, and Cardiac Shock: A Case Report

Abstract: We report a 49-year-old man, without prior medical history, consulted in the emergency department with a 5 day history of cough, fever, and dysuria. He was admitted to the intensive care unit due to septic shock. Critical care management was initiated, including mechanical ventilation and vasopressors. Endotoxic shock was suspected (endotoxin activity assay [EAA] 0.75), and 2 treatments with Polymyxin B hemoperfusion (Toraymyxin ® , Toray Medical Co., Ltd., Tokyo, Japan) were performed in 48 h, alternate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…After excluding irrelevant articles (i.e., reviews, meta-analyses, protocols, letters), 60 studies were retrieved ( Figure 2 ). Of these, 22 were excluded due to their focus on veno-arterial ECMO (V-A ECMO) or extracorporeal cardiopulmonary resuscitation (ECPR) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Fourteen studies were excluded for lack or scarcity of data on CytoSorb© use [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], four because of the lack of specific data for the ECMO subgroup [ 67 , 68 , 69 , 70 ], four because CytoSorb© was not used concomitantly with ECMO therapy [ 71 , 72 , 73 , 74 ], two because outcomes of interest for the simultaneous use of CytoSorb© and ECMO were not reported [ 75 , 76 ], and one because it focused on a different device [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…After excluding irrelevant articles (i.e., reviews, meta-analyses, protocols, letters), 60 studies were retrieved ( Figure 2 ). Of these, 22 were excluded due to their focus on veno-arterial ECMO (V-A ECMO) or extracorporeal cardiopulmonary resuscitation (ECPR) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Fourteen studies were excluded for lack or scarcity of data on CytoSorb© use [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], four because of the lack of specific data for the ECMO subgroup [ 67 , 68 , 69 , 70 ], four because CytoSorb© was not used concomitantly with ECMO therapy [ 71 , 72 , 73 , 74 ], two because outcomes of interest for the simultaneous use of CytoSorb© and ECMO were not reported [ 75 , 76 ], and one because it focused on a different device [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the successful implementation of the renal replacement therapy, the last decade has witnessed a great advance in blood purification techniques. As the frontline of multiple organ support, extracorporeal organ support [17], including VV-ECMO, ECCO2R, VA-ECMO, intermittent and continuous HD, hemofiltration, hemodiafiltration, hemoperfusion, plasmapheresis, and sorbent therapies, has served its role in life support and provided an opportunity to improve patient outcomes in critical care settings [18-20]. It was reported that 5% of the confirmed cases was in need of intensive care during the COVID-19 outbreak [21].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Initial reports in the treatment of chronic dialysis patients and of chronic liver patients with pruritus have been encouraging [ 49 , 75 ]. At the same time, clinical applications of sorbents in sepsis , acute kidney injury, and other inflammatory states have provided useful data on feasibility and safety, forming the basis for future technical, procedural, and manufacturing optimization [ 58 , 76 , 77 ].…”
Section: The Hemoperfusion Research Agenda and Recommendationsmentioning
confidence: 99%